(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
The Ddureb’ Brandberg, Namibia’s highest mountain, is one of the most weJI documented rock art regions in the world. All in a/1 almost 900sites comprising of almost 50 ooo individual images were recorded in the Ddureb. However the rock engravings’ which have been found in the Dome Gorge remain relatively sparsely researched. The Dome Gorge is a unique site in the sense that paintings and engravings converge and in some cases superimpose each other. The aim of this research was to understand the entire corpus of the area through conducting empirical documentation of the site. Altogether seven different types of combinations of engravings and paintings were observed in the data. The study a/so investigated the spatial patterning of the rock engravings in the Dome Gorge and established an empirical description of the distribution and Jiguration of engravings based on quantitative analysis.